Literatura digital : ampliando as possibilidades de letramentos no ciberespaço a partir do gênero hiperconto - Souza, José Batista de (2019)
This Work of Final Conclusion (TCF) presents a pedagogical intervention proposal destined to the realization of practices that promote different literacies on part of the students of Elementary School II, participators of 9th grade, of a school of public school system of the municipality of Coronel João Sá, Bahia. Based on these considerations, the current work has as goal to improve the teaching of Portuguese Language, specifically, the teaching of textual production, through the digital gender hiperconto. In the contemporaneity, the reader needs to be a multiletrado citizen that, besides the printed text, he has the digital as source of diverse possibilities of literacies. The hiperconto, due to the multisemiology present in it, it is one of the possibilities capable of transfigure the reader (CHARTIER, 2002), making him leave of a position less interactive (as an overview in relation to printed texts), to a more interactive (construction and textual reconstruct in the digital scope). In this context, the methodology adopted in the current work is the theoretical research (RAMPAZZO; CORRÊA, 2008), and the action research (THIOLLENT, 2002; SEVERINO, 2016), that aims to the intervention and resolution of questions, in these case, the problems related to the textual production. We discussed, along the work the dichotomy between digital literature and digitalized literature (BRAGA; RICARTE, 2005; SPALDING, 2012); the literacy (KLEIMAN, 2005; SOARES, 1998, 2016); the digital literacy (BUZATO, 2006; BRAGA, 2010; FREITAS, 2010); the multiliteracies (COPE; KALANTZIS, 2000; ROJO, 2012); the hiperconto (SPALDING, 2010), and the hypertext (GOMES, 2011). The intervention proposal is configured in four stages, organized through the workshops of reading and production (PAVIANI; FONTANA, 2009). In the first stage, we make a reading and discussion about the tale and its characteristics, followed by a brief debate about technology and writing, performed to the introduction of a link to a hiperconto; in the second, we present the gender hiperconto in the classroom, through the digital medias, calling the attention to the similarities and differences between the two genders; in the third stage, in the informatics laboratory of the school, the students explore the digital gender hiperconto, in some sites of the cyberspace, specialized in digital literature, surf and check all the wealth, dynamism and creativity that such productions enable in this new conception of reading on screen, expanding this exploitation out of the school; in the fourth stage, (this more long), through a collaborative work, the students produce some hipercontos to be published in a site created to this purpose through the platform Wix. In the final of this proposal, the results pointed that the students passed to write more, not only in the printed support but also in the digital, they improved their written productions through all the stimulus enabled for the digital literature represented by the hiperconto, achieving, that way, a significant improvement in the textual production, with emphasis to the progression of the writing.